(untitled) (Yangi O’zbekiston taraqqiyotida tadqiqotlarni o’rni va rivojlanish omillari, 2024)
his article provides information about the concept of social status, its definitions in sociology, psychology, and its main features. The essence of this concept has also been discussed in linguistics. Pragmatic, sociolinguistic views on the concept of social status, opinions on speech communication are described.